Perubahan Luasan Lahan Mangrove Sebagai Ruang Terbuka Hijau Di Wilayah Pesisir Kota Bandar Lampung - Maurent Kartika Maharani; Indra Gumay Febryano; Novita Tresiana; Irwan Sukri Banuwa (Universitas Bangka Belitung, 2021)
Coastal areas have many functions such as phisical, ecological, and economic with the existence of mangrove inside. The objective of the study is to find out the changes in mangrove area in Karang City. The method which is used in this study is the image interpretation tecnique with Geographic Information System (GIS) to the changes in area in 2012, 2015, 2017, and 2019. The data of mangrove’s extensive changes are analyzed by the result of direct interview on the changes in area that occur to find out the cause of the changes in mangrove area. The result shows that in 2015, there was a decrease in mangrove area of 0.4781 ha due to the development of coastal area to Pasaran Island. In 2017-2019, the increase occurred due to the ability of Mangroves to adapt with their habitat so that area increased towards the ocean of 1,193 ha. The increase of mangrove in the urban coastal areas can be considered to be designated as a green open space in addition to coastal conservation area and small islands.